Cryptosporidiosis among birds and bird handlers at Zoo Negara, Kuala Lumpur / Muhamat Shukri Mahat - Muhamat Shukri , Mahat (2006)

(untitled)
This study was carried out at the Malaysian National Zoo to ascertain not only the current prevalence rate in the birds but also to determine the association between cryptosporidiosis in birds and the bird handlers. 116 fecal samples from 71 species of birds were collected from six different locations in Zoo Negara and 8 fecal samples from bird handlers were also sampled. Results showed that the prevalence of Cryptosporidium oocysts in bird and bird handlers were 3.4% (4 out of 116 samples) and 12.5% (1 out of 8 samples) respectively. The birds that were positive for cryptosporidiosis were Wreathed Hornbill (Aceros undulates) and Great Currasaw (Crax rubra) from the aviary, Bushy-crested Hornbill (Anorrhinus galeritus) from the bird house and Common Peafowl (Pavo Cristatus) from the lake. Birds at the lake showed the highest percentage (12.5%) of being positive followed by birds at the aviary (5.4%) and birdhouse (2.8°10). Results of the present study seemed to indicate that cryptosporidiosis might be spreading to other species of birds (a comparison with a similar study conducted in 2004) and to other locations in the zoo which was not previously documented. This study also discovered the probable association of cryptosporidiosis among birds and bird handlers. However conclusive remarks can only be done after the confirmation of speciation found in birds and bird handlers through molecular identification.